Development of Mobile Learning Using Contextual Teaching and Learning Approach to Improve Mathematical Communication Skills of High School Students - M.Taufik Akbar; Jefri Marzal; Yantoro (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Students' low mathematical communication skills are the main problem that needs to be addressed by an educator. Learning should be designed through problems that allow students to communicate mathematically better. This study aims to produce mobile learning-based learning media with a Contextual Teaching and Learning approach that is valid, practical, and effective for improving students' mathematical communication skills. The subjects of this study were tenth-grade students of SMA Negeri 8 Batang Hari in the even semester of 2024/2025. This type of research is Research and Development with the ADDIE model. The results of this study indicate that the quality of the developed mobile learning learning media has valid, practical, and effective categories. Validity can be seen from the results of expert validation in the fields of media and learning materials, which show that mobile learning is good and feasible to use. Practicality can be seen from the perceptions of students and teachers who gave positive responses to the developed mobile learning, and effectiveness can be seen from the increase in students' mathematical communication skills with a comparison of pre-test and post-test results using the N-Gain test with a score of 0.71 in the high category. Thus, to improve students' mathematical communication skills, mobile learning with the contextual teaching learning approach that has been developed can be used.